A handbook of Middle English studies - Turner, Marion (Chichester, West Sussex, UK : Wiley-Blackwell, A John Wiley & Sons, Ltd., Publication, 2013)
"A Handbook to Middle English Studies presents a series of original essays from leading literary scholars that explore the relationship between critical theory and late medieval literature. This book: Includes 26 new essays by leading scholars of late medieval literature ; Sets the new standard for an introduction to the study of late medieval literature ; Showcases the most current cutting-edge theoretical research ; Demonstrates a range of approaches to late medieval literature ; Brings together critical theory and medieval literature."--Publisher's website.
Introduction / Marion Turner. -- Part 1: Selfhood and Community. Imagination / Aranye Fradenburg ; Memory / Anke Bernau ; Desire / Elizabeth Scala ; Gender / Nicola McDonald ; Sexuality / Glenn Burger and Steven F. Kruger ; Public Interiorities / David Lawton ; Race / Jeffrey Jerome Cohen ; Animality / Susan Crane. -- Part 2: Constructing Texts, Constructing Textual History. Authorship / Vincent Gillespie ; Audience / Joyce Coleman ; Manuscript / Alexandra Gillespie ; Material Culture / Jessica Brantley ; Genre / Julie Orlemanski ; Aesthetics / Maura Nolan ; Canon Formation / Thomas A. Prendergast ; Periodization / David Matthews. -- Part 3: Politics and Places. Sovereignty / Robert Mills ; Class / Isabel Davis ; Church / Laura Varnam ; City / Jonathan Hsy ; Margins / Corinne Saunders ; Ecology / Carolyn Dinshaw ; Nation / Kathy Lavezzo ; Language / Laura Ashe ; Postcolonialism / John M. Ganim ; A Global Middle Ages / Geraldine Heng.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 1100 - 1500; English literature -- Middle English, 1100-1500 -- History and criticism; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature -- Middle English; Electronic books; Criticism, interpretation, etc